The Influence of Interpersonal Communication and Internship Experience on the Work Readiness of Students of the Faculty of Economics and Business, Padang State University: Pengaruh Komunikasi Interpersonal Dan Pengalaman Magang Terhadap Kesiapan Kerja Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Negeri Padang - Mutiara Annisa; Dessi Susanti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Aimed to analyze how interpersonal communication and internship experience affect job readiness among students. This research emerged from the pressing issue of elevated unemployment rates among university graduates, stemming from inadequate preparation and a dearth of relevant experiences. This quantitative study employed questionnaires to measure levels of interpersonal communication, internship experience, and job readiness. The participants in the study were drawn from the vibrant community of students at the Faculty of Economics and Business at the University of State Padang. A thorough statistical analysis was undertaken to delve into the intricate relationships among a range of variables. The findings revealed notable beneficial impacts of interpersonal communication and internship experience on job readiness. Students with good interpersonal communication skills and meaningful internship experiences demonstrated higher preparedness for entering the workforce